The potential effect of different types of flaxseed (Linum usitatissimum) extract on the cell viability of oral fibroblasts human cell line - Naziyah Shaban, Sama; Mokhtar@Makhtar, Khairani Idah; Arief Ichwan, Solachuddin Jauhari; Mustafa Al-Ahmad, Basma Ezzat (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2019)
Herbal medication and natural products have been successfully demonstrated to have general health beneficial effects. The bioactivities of flaxseed (linum usitatissimum) extract have been reported, as previous studies have shown that l. usitatissimum extract has many health and beneficial effects such as antimicrobial, anti-oxidant and anti-inflammatory effect. L. usitatissimum extract makes a great skin wound healing agent in addition to that it has good effect on the oral cavity in treating ulcers and general oral health benefits. L. usitatissimum is extracted using ethanol in three different concentration via soxhlet method, gas chromatography mass spectrum (GC-MS) is used to illustrate the components of l. usitatissimum extract. 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay is used to assess the oral fibroblasts cell viability in three different time lines. The results illustrate the major component present in l. usitatissimum extract and the effect of the different ethanol concentrations of flaxseed extract on oral fibroblasts human cell line. L. usitatissimum extract show proliferating effect, the 70% flaxseed ethanolic extract produced the highest proliferating effect on fibroblast cells at 24 hours followed by 100% followed by 90% ethanol flaxseed extract, at 48 hours and 72 hours 100% ethanoic extract produced the highest proliferating effect followed by 70% then 90% ethanol flaxseed extract. The results show proliferating effect by l. usitatissimum extract on human oral fibroblast cell line.